If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(x+2/x+6)+1=(x+4/x+2)
We move all terms to the left:
(x+2/x+6)+1-((x+4/x+2))=0
Domain of the equation: x+6)!=0
x∈R
Domain of the equation: x+2))!=0We get rid of parentheses
x∈R
x+2/x-((x+4/x+2))+6+1=0
We calculate fractions
x+2x/x^2+(-((x+4*x)/x^2+6+1=0
We add all the numbers together, and all the variables
x+2x/x^2+(-((+5x)/x^2+6+1=0
We calculate fractions
We do not support expression: x^4
| 16– 4w=24 | | x+2/x+6+1=x+4/x+2 | | 8x^2=6+9x | | (24x+12)/3+2x=(0,5x+11)·2-1+19 | | 6x+3=7+3x | | 7k^2+3k=-1 | | 2(6x^2-3)=11x^2-x | | 11x^2+12x=24 | | 98/3=-7/2(n-10/3)-5/2n | | 2(3x+5)-4x=4(6x+3)/2-6 | | (y-14)(y+4)=y-14 | | 10x^2+11=4x | | 2t^2-30t=-52 | | F(-x)=3x^2-5x+4 | | s^2=6s-9 | | 2x+8=-6x+9 | | 48-3x=6 | | 7x+1/2=11 | | 2x^2=6-2x | | 12m^2-1=-3m | | (4x+1)²=0 | | F=7/6(n-29) | | -78=-19x+x^2 | | Y+(y-5)=75 | | 5x-2(x+3)=2(x+4) | | 59h=190-45h | | -3x(7-2x)=0 | | (D^5-D^3)y=0 | | 6n^2=20+6n | | 3y^2=16y | | 3/4x+2/5x=92 | | 6x+2=7-2x |